Pengaruh Live Streaming, Flash Sale dan Promo Gratis Ongkir terhadap Perilaku Impulsive Buying pada Pengguna Aplikasi Tiktok - Putri, Sissy Jania; Yadewani, Dorris; Rahayu, Sari (Pustaka Galeri Mandiri, 2025)
This study aims to determine live streaming, flash sale and free shipping promo on impulsive buying behavior. This study uses a causal associative research type with a quantitative approach and a probability sampling method with the Stratified Sampling technique on 89 respondents who use the TikTok shop application. Data were collected through questionnaires and processed using SPSS. The test results show that (1) Live Streaming does not have a significant effect on Impulsive Buying Behavior in TikTok shop application (2) Flash Sale has a significant effect on Impulsive Buying Behavior in TikTok shop application users (3) Free Shipping Promo has a significant effect on Buying Behavior. This finding indicates that students need to improve their awareness and financial management skills in dealing with impulsive offers, while for companies, it is important to optimize marketing strategies such as flash sales and free shipping promos, as well as develop more interesting live streaming content to attract students' attention.